Patient participation as dialogue: setting research agendas. - Abma TA; Broerse JEW (Health Expectations, 2010)
Background Collaboration with patients in healthcare and medical research is an emerging development. We aimed to develop a methodology for health research agenda setting processes grounded in the notion of participation as dialogue. Methods We conducted seven case studies between 2003 and 2007 to develop and validate a Dialogue Model for patient participation in health research agenda setting. The case studies related to spinal cord injury, neuromuscular diseases, renal failure, asthma/chronic obstructive pulmonary disease, burns, diabetes and intellectual disabilities. Results The Dialogue Model is grounded in participatory and interactive approaches and has been adjusted on the basis of pilot work. It has six phases: exploration; consultation; prioritization; integration; programming; and implementation. These phases are discussed and illustrated with a case description of research agenda setting relating to burns. Conclusions The dialogue model appeared relevant and feasible to structure the process of collaboration between stakeholders in several research agenda setting processes. The phase of consultation enables patients to develop their own voice and agenda, and prepares them for the broader collaboration with other stakeholder groups. Challenges include the stimulation of more permanent changes in research, and institutional transitions.